CCR1 antagonist ameliorates experimental autoimmune encephalomyelitis by inhibition of Th9/Th22-related markers in the brain and periphery. (April 2022) - Al-Mazroua, Haneen A.; Nadeem, Ahmed; Ansari, Mushtaq A.; Attia, Sabry M.; Bakheet, Saleh A.; Albekairi, Thamer H.; Ali, Nemat; Alasmari, Fawaz; Algahtani, Mohammad; Alsaad, Abdulaziz M.S.; Ahmad, Sheikh F.
Abstract: Multiple sclerosis (MS) is an immune-mediated disease of the central nervous system. The disease manifestation is associated with the proliferation and activation of lymphocytes and astrocytes, leading to demyelination and neuronal damage. Most of the current therapies are not completely effective, and few target the underlying pathophysiology of MS. T helper 9 (Th9)- and Th22-dominant cells have been proven to play a pathogenic role in experimental autoimmune encephalomyelitis (EAE), an animal model of MS. The goal of the present study was to investigate the therapeutic efficacy of J-113863, a novel CCR1 chemokine receptor, on PLP139–151 -induced EAE in SJL/J mice. Following induction of EAE, mice were treated with J-113863 (10 mg/kg) or saline intraperitoneally daily from day 14 until day 25, and the clinical score was evaluated. We further investigated the effect of J-113863 on IL-9, IRF4, IL-22, IFN-γ, STAT3, AhR, and IL-17A in CD3 +, CD4 +, CCR6 +, and CCR8 + spleen cells using flow cytometry. We also analyzed the effect of J-113863 on IL-9, IRF4, IL-22, IFN-γ, STAT3, AhR, and IL-17A mRNA expression levels. Our results revealed that J-113863 treatment notably attenuated the severity of clinical scores in EAE mice. J-113863 treatment decreased the percentage expression of CD4 + IL-9 +, CCR8 + IL-9 +, CD4 + IRF4 +, CD3 + IL-22 +, CCR6 + IL-22 +, CD3 + IFN-γ +, CCR6 + IFN-γ +, CD3 + STAT3 +, CCR6 + STAT3 +, CD4 + IL-17A +, and CCR6 + IL-17A +, and increased the percentage of CD3 + AhR +, and CCR6 + AhR + cells in the spleen. These results confirmed that J-113863 suppressed Th9/Th22 cells to reduce demyelination in EAE mice, suggesting its potential role as a novel drug candidate for MS treatment. Highlights: We investigated the possible neuroprotective effects of J-113863. J-113863 attenuates clinical symptoms of EAE mice. J-113863 inhibits Th9 cells in the brain and periphery. J-113863 downregulates Th22 signaling in EAE mice. J-113863 could be a therapeutic candidate for MS.